Pilot study examining anti-factor Xa levels for heparin monitoring and outcomes in patients with cerebral venous thrombosis - Pirahanchi, Yasaman; Salottolo, Kristin; Burrell, Christian; Tang, Xu; Bar-Or, David; Bartt, Russell (Frontiers in Medicine, 2024)
Objective: There are no studies to date that examine the association between antifactor-Xa (AFXa) based heparin monitoring and clinical outcomes in the setting of cerebral venous thrombosis (CVT). Methods: This pilot study included adults ≥18 admitted with CVT between 1/1/2018-1/1/2021, who were treated with UFH, and were monitored using AFXa-based nomogram within 24 hours of arrival. Comparisons were made between patients who were in target therapeutic range (AFXa, 0.25 -0.5 IU/mL) and patients who were not in therapeutic range within 24h of arrival, as well as the time (hours) from arrival to reach therapeutic range. Outcomes were hospital length of stay (LOS), major (actionable) bleeding events, and discharge home (vs. higher acuity location). Continuous data are presented as median (interquartile range). Results: Among 45 patients, treatment with UFH was initiated 2 (1-11) hours from arrival and the majority (84%) of UFH infusions did not need dose adjustment. AFXa assays were drawn every 6 (5.5-7) hours. Thirty (67%) patients were in therapeutic range. Outcomes were similar for patients in therapeutic range vs. not in range: major bleeding events, 10% vs. 0% (p=0.54); discharge home, 77% vs. 80% (p=1.0); hospital LOS (5 days in each group, p=0.95). There was also no association between outcomes and time to reach therapeutic range. Conclusions: Our findings demonstrate the practicability of monitoring UFH based on AFXa values in this population of patients with CVT, but reaching target AFXa levels within 24 hours of arrival may not necessarily be prognostic.